Fifteen years of military research in five military schools and in the National Defense College of the Philippines, 1966-1980 an analysis with an annotated bibliography - Parajas, Mary Lou R.; Vallejo, Rosa M.; Agtay, Melecio T. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1983)
The purpose of this study is to bibliographically control military researches conducted in five AFP schools and the National Defense College of the Philippines, classify the available military researches according to the AFP Subjective Classification System and establish where they are located. This compilation of researches from 1966 to 1980 further gives an insight on the frequencies of studies conducted in various AFP subject areas.
The study covers only the output of students in fulfillment of course requirements in the form of theses, staff studies, special studies and/or term papers produced by the following courses, namely: Naval Staff Course of the Philippine Navy Naval Training Command, Squadron Officer's Course; Associate Advanced Medical Service Officer's Course of the AFP Medical Center; masteral degree course in National Security Administration (MNSA) of the National Defense College of the Philippines and the General Staff Course of the AFP Command and General Staff College.
A bibliographic search for materials at the University of the Philippines, The National Library and the different AFP libraries to include the Philippine Military Academy was conducted. Likewise, letters to the AFP librarians were handcarried and several persons were interviewed to elicit responses to two questions on librarianship. A total of 2,319 studies were produced for the last fifteen years. Of this number, 1,253 are considered unclassified, while 1,066 are classified and are not generally accessible to the general public. The classified works are also not listed nor reflected in the card catalogs of libraries surveyed. For this study, only the unclassified works are included pursuant to the provisions of AFP Regulations G200-013. The results of this study on military research conducted in the six military schools show that the products of student research form a major part of the library's collection because most of the schools provide copies to the libraries. The libraries that do not regularly receive copies are the Medical Service School, the Naval Training Command, and the PC/INP Command. Most of the collections are not organized, no lists or records of the research works are available.
The requirements for each course differ from school to school and from year to year. Not all courses require a research study for completion, e.g., Naval Staff Course and the Philippine Army Officer Senior Course. Likewise, the nomenclature of these research studies vary from school to school. They are variously called as staff studies, term paper, special studies or thesis. NDCP requires a thesis from the 10th class onwards for the MNSA degree; AFPCGSC requires staff studies and/or special studies and later a thesis; while PAF requires only a staff study. This affects the quality of research produced. Research study is also done by individual students or by a group of students.
The study found out that the most popular method of research used is the historical method or a combination using also the historical method. On the other hand, it was found that duplication of research occurred in the AFPCGSC and the ACGSC on seven subjects, namely; Family Planning; Foreign Officer's Exchange Program; Fear, Rumor and Panic; Narcotics; and Methods of Detecting Leadership Traits and Techniques for Application to Selection of Potential Division Commanders.
The most frequently researched area or subjects are Operations and Training; Administrative Management; Personnel Administration; Government and Civil Affairs; Sciences Research and Development; Supply and Services; Buildings and Grounds; Intelligence and Security; and Finance and Accounting. These subjects are more allied to the school's curriculum and the needs of the parent service unit to which the student officer belongs. On the other hand, the least researched subjects are Medicine and Dentistry; Police Administration; Transportation and Communications; Aviation and Aeronautics; Legal Administration; Rivers, Harbors and Waterways; and Maps, Photographs and Charts.
While all the libraries are open to those who are in need of information, the majority of users come from the military schools. Classified materials are available to those who have the requisite clearances for its use. All libraries provide adequate library services which is their primary objective.
In conclusion, this study affirms the need for a bibliography of military researches as a basic research tool to help the ever-increasing number of researchers and library users save time and effort in locating needed references.
Mimeographed.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Military research -- Bibliography. -- Philippines; National Defense College of the Philippines